Effects of Urinary Kallidinogenase on NIHSS score, mRS score, and fasting glucose levels in acute ischemic stroke patients with abnormal glucose metabolism: A prospective cohort study. Issue 35 (August 2019) - Chen, Lei; Geng, Lianxia; Chen, Junmin; Yan, Yan; Yang, Lan; Zhao, Jing; Sun, Qian; He, Junna; Bai, Lin; Wang, Xiaopeng
Abstract : Abstract: Urinary kallidinogenase may assist recovery acute ischemic stroke. This study evaluated the effect of urinary kallidinogenase on National Institute of Health Stroke Scale (NIHSS) score, modified Rankin scale (mRS) score, and fasting glucose levels in patients with acute ischemic stroke (AIS) combined with diabetes mellitus and impaired fasting glucose. Patients with AIS and abnormal glucose metabolism were enrolled in this prospective cohort study and divided into 2 groups. The human urinary kallidinogenase (HUK) group were treated with urinary kallidinogenase and standard treatment; the control group received standard treatment. NIHSS scores, mRS scores, and fasting blood glucose were evaluated and compared. A total of 113 patients were included: 58 in the HUK group and 55 in the control group. NIHSS scores decreased with treatment in both groups (time effect P  < .05), but were lower in the HUK group (main effect P  = .026). The mRS score decreased in both groups from 10 until 90 days after treatment (time effect P  < .05); the 2 groups were similar (main effect, P  = .130). Blood glucose levels decreased in both groups 10 days after treatment (time effect, P  < .05), but there was no significant treatment effect (main effect, P  = .635). Multivariate analysis showed blood uric acid >420 μmol/L (odds ratio [OR]: 0.053, 95% confidence interval [CI]: 0.008–0.350; P  = .002) and application of HUK (OR: 0.217, 95% CI: 0.049–0.954; P  = .043) were associated with 90% NIHSS recovery. Baseline NIHSS score was independently associated with poor curative effect. Urinary kallidinogenase with conventional therapy significantly improved NIHSS scores in patients with AIS. Urinary kallidinogenase also showed a trend toward lower fasting blood glucose levels, although the level did not reach significance.